TNI Influence Operation and Information Warfare Force; Noopolitik Perspective - Maulaya, Mahbi; Wafi, Fadhlil (The Republic of Indonesia Defense University, 2025)
The news about the Indonesian National Army’s, or Tentara Nasional Indonesia (TNI), budget for internet buzzers has led to public disapproval. This disagreement shows how the public is still unfamiliar with the idea that Influence Operations and Information Warfare (IOIW) is now a thing in national security and defense strategy. This article aims to make sense of why TNI should consider the IOIW capability. With the library research method, this article introduces the conceptual and theoretical argument of Noopolitik and IOIW to the Indonesian policymakers and the general public. Noopolitik is a concept explaining the existence of the noosphere, a world